Organic fertilizer and irrigation in changes the chemical properties of a Fluvent and okra production - Mesquista, Evandro Franklin de; Chaves, Lúcia |Helena Garófalo; Melo, Emanuela Candida; Cavalcante, Lourival Ferreira; Alves, Anailson Sousa; Lima santos, Albanisa Pereira (Comunicata Scientiae, 2018)
The objective of this experiment was to evaluate the effect of organic fertilization on changes of chemical properties of a “Neossolo Flúvico Eutrófico” (Fluvent) and okra production, cultivated with and without mulching and irrigation depths. The experiment was installed in the Agroecology sector at Universidade Estadual da Paraíba. The treatments were designed in a randomized blocks using the 2 x 5 x 2 factorial, which  corresponding to two irrigation depths (100 and 50% of the crop evapotranspiration - ETc), five doses of cattle manure to increase the level from 1.8 % to 2.8; 3.8; 4.8 and 5.8%, in soil with and without mulching (plant residues), with four replications, totaling 80 plots with 27 plants per plot. 140 days after planting okra, soil samples were collected at each plot and chemical analyses were performed. The okra production was evaluated based on the number of green fruits and crop yield. The data were submitted to analysis of variance. The application of cattle manures to the soil between 4.8 and 5.8% and irrigation with 100% of crop evapotranspiration - Etc, with and without mulching, was suitable for the cultivation of okra under semi-arid climatic conditions, which provided increases in the chemical attributes of a Fluvent and in the okra production.